A Review on Green Building in Vietnam. (2016) - Nguyen, Hong-Trang; Gray, Matthew
Abstract: Following market reforms in 1986 Vietnam has transformed from a poor closed economy to a low middle income economy. Like other developing countries, economic growth has placed significant pressure on both infrastructure and environment, particularly the pressure of increasing housing demand, energy consumption, and waste and pollution management. In response to the development challenges and the green movement globally, the government has initiated actions to promote green building to promote more sustainable development. However, green building adoption in Vietnam is still criticised as being slow and lacking governmental support. This paper proposes that promoting green building could solve three inter-connected challenges hindering sustainable development, and provides a comparative review of progress.